Determinants of Absenteeism Among Undergraduate Medical Students: A Cross-Sectional Study from a Public Medical College in Pakistan - Hameed, Imad; Ahmad, Miraj; Ali, Ghazanfar; Ullah, Niamat; Ullah, Fida; Rabi, Fazal E (ADVANCES IN BASIC MEDICAL SCIENCES, 2025)
OBJECTIVE: To identify the determinants of absenteeism among undergraduate medical students at a public medical college in Pakistan, focusing on academic, psychological, and social factors. METHODOLOGY: This cross-sectional study was conducted at Bacha Khan Medical College (BKMC), Mardan, from December 2024 to March 2025. A total of 200 MBBS students with attendance below 75% were enrolled through convenience sampling. Data were collected using a validated, self-administered questionnaire that covered academic stress, mental health, teaching satisfaction, learning engagement, and social influences. Statistical analysis included descriptive statistics, chi-square tests, and binary logistic regression. RESULTS: Key contributors to absenteeism included academic stress (78%), dissatisfaction with teaching methods (70%), mental health issues (65%), low engagement (60%), and social factors (52%). Logistic regression identified academic stress (OR = 2.78, p < 0.001), low engagement (OR = 2.43, p = 0.001), mental health issues (OR = 1.94, p = 0.018), dissatisfaction with teaching (OR = 1.88, p = 0.021), and social influences (OR = 1.67, p = 0.045) as significant predictors. No significant associations were found with gender or academic year. CONCLUSION: Absenteeism among medical students in public-sector institutions in Pakistan is influenced by multiple interrelated factors, particularly academic stress and disengagement. Addressing these issues through institutional reforms, enhanced teaching methods, and mental health support could improve student attendance and overall academic performance.